Effect of Early Ability, Learning Independence, and Attitude of Confidence Towards Student Involvement - Firmannandya, Ade (Universitas Trunojoyo Madura, 2023)
Many schools and universities in Indonesia have implemented combination learning or blended learning. Many factors influence student involvement in blended learning, including initial abilities, independent learning, and student attitudes. This study aims to determine the effect of initial abilities, learning independence and self-confidence on student involvement in blended learning. The initial ability variable is measured from the aspect of skills in using information technology, the willingness to use information technology, the availability of information technology, and confidence in the reliability of information technology. Learning independence is measured by not depending on others, disciplined behavior, a sense of responsibility, behaving based on initiative, and exercising self-control. The attitude variable of self-confidence is measured by confidence in using information technology, asking and answering questions, expressing opinions, and completing tasks on their own. Student involvement in online learning is viewed from 3 dimensions, namely cognitive, emotional and behavioral involvement. This study uses a non-experimental quantitative research design and is analyzed using Partial Least Square (PLS). Data was collected using a questionnaire and distributed to students in Indonesia. The study results show that learning using blended learning initial abilities, learning independence, and self-confidence affect student involvement.